Fibras de celulose modificadas superficialmente pela técnica de plasma frio assistida por micro-ondas: desenvolvimento e aplicações - Henrique, Mariana Alves (2019)
In this work the filter papers were subjected to surface modification using microwave assisted plasma technique. The papers were subjected to different atmospheres of steam, such as argon, oxygen and different alcohols (methyl, ethyl, isopropyl, butyl and benzylic). These papers were characterized before and after modifications in terms of: surface energy by contact angle measurements, Fourrier pro-transform infrared (FTIR) analysis, X-ray excited photoelectron spectroscopy (XPS), scanning electron microscopy SEM), X-ray analysis and roughness study by atomic force microscopy (AFM). It was observed a great hydrophobization of the filter papers, evidenced by the changes in the values of the surface energies, the increase of the angle of contact with the water and the increase of the roughness values. By X-ray analysis it was found that the basic structure of the cellulose fibers of the filter paper remained unchanged. By FTIR analysis it was not possible to observe chemical changes in the structure of the cellulose, but by XPS an increase in the amount of C1 in the surface of the modified papers was observed in relation to the paper without modification, evidencing chemical modification. From SEM and AFM analysis, we can see the formation of nanostructures on the surface of the paper fibers, which allied to the grafting of alcohol molecules, can be responsible for the high hydrophobicity observed from values of contact angle with water from 43 ° for the untreated paper up to 126 ° for the treated papers. From the results observed, papers modified for enzymatic immobilization were used, which presented an average of 70% immobilization.